166k views
1 vote
Which equation is equivalent to ( 1/3)^x= 27^x+2?

3x = 3-3x+2
3^x=3^3x+6
3^-x=3^3x+2
3^-x=- 3^3x+6

User Shone
by
5.2k points

2 Answers

4 votes

Answer:

3^-x=3^3x+2

Explanation:

To get the equivalent of ( 1/3)^x= 27^x+2 . we need to expand the expression.

( 1/3)^x= 27^x+2

Base on the law of indices

( 1/3)^x = 3^-x

Then

27^x+2 can be expanded as

3^3x + 2

Bringing the expression together

3^-x = 3^3x + 2

User Sami Kanafani
by
5.9k points
0 votes

Answer:

The the equation equivalent to given equation is
(3)^(-x) = (3)^(3x)+ 2

Explanation:

Given Equation as :


((1)/(3))^(x) = 27^(x)+ 2

Or,
((1)/(3))^(x) =  (3^(3))^(x)+ 2

Or,
(3)^(-x) = (3)^(3x)+ 2

Hence The the equation equivalent to given equation is
(3)^(-x) = (3)^(3x)+ 2 Answer

User Jaspernygaard
by
6.2k points